2020
DOI: 10.1111/ejn.14875
|View full text |Cite
|
Sign up to set email alerts
|

Visual behaviors in disorders of consciousness: Disentangling conscious visual processing by a multimodal approach

Abstract: One of the major challenges for clinicians who treat patients with Disorders of Consciousness (DoCs) concerns the detection of signs of consciousness that distinguish patients in Vegetative State from those in Minimally Conscious State. Recent studies showed how visual responses to tailored stimuli are one of the first evidence revealing that one patient is changing from one state to another. This study aimed to explore the integrity of the neural structures being part of the visual system in patients with DoC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The GCS and the CRS-R were equally applied for diagnosis and were mostly used to diagnose VS/UWS patients. Seven papers considered EEG and metabolic data (FDG-PET; SPECT), while seven papers compared EEG data with both MRI and PET information (Carriére et al, 2020;Ferraro et al, 2020;Forgacs et al, 2014;Hermann et al, 2020;Laureys et al, 2002;Sattin et al, 2020Sattin et al, , 2021. Only Laureys et al (2002) included VS/UWS patients assessed by GCS; all the other six studies used the CRS-R to diagnose mixed DoC patients (VS/UWS, MCSÀ/+, EMCS).…”
Section: Eeg-based Multimodal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The GCS and the CRS-R were equally applied for diagnosis and were mostly used to diagnose VS/UWS patients. Seven papers considered EEG and metabolic data (FDG-PET; SPECT), while seven papers compared EEG data with both MRI and PET information (Carriére et al, 2020;Ferraro et al, 2020;Forgacs et al, 2014;Hermann et al, 2020;Laureys et al, 2002;Sattin et al, 2020Sattin et al, , 2021. Only Laureys et al (2002) included VS/UWS patients assessed by GCS; all the other six studies used the CRS-R to diagnose mixed DoC patients (VS/UWS, MCSÀ/+, EMCS).…”
Section: Eeg-based Multimodal Studiesmentioning
confidence: 99%
“…Fourteen studies explored the underlying neuropathological mechanisms of consciousness by observing rs-fMRI (Kim et al, 2021;Mikell et al, 2015;Snider et al, 2022) or neurometabolic (Hildebrandt et al, 2007) data by testing patients' responsiveness to external auditory (Laureys et al, 2000), or noxious somatosensory (Laureys et al, 2002), or visual stimuli (Sattin et al, 2020(Sattin et al, , 2021 or by arousing cognitive active paradigms (Bekinschtein et al, 2011;Chennu et al, 2013;Curley et al, 2018;Edlow et al, 2017;Gibson et al, 2016). Most of these studies suggested that combining information from different approaches should help in detecting the brain networks required to support conscious processes.…”
Section: Studies Investigating the Neural Correlates Of Consciousnessmentioning
confidence: 99%
“…Patients were clinically assessed with the Italian version of the Coma Recovery Scale-Revised CRS-R) [35,36] and with the CRS-R-Modified score [37]; each patient was independently assessed 4 times by experienced raters and the best response was used to establish the final score. Patients also underwent a multimodal assessment comprising evoked potentials (EPs) to assess the presence/absence of the visual, auditory and sensory pathways (as reported in [38]) and FDG-PET, to have a measure of metabolism (as reported in [24,39,40]).…”
Section: Participantsmentioning
confidence: 99%
“…Recent studies have also employed combined modalities to pinpoint the neural correlates of a specific behavior. Differences in brain activity between patients with visual pursuit and those with only a reflexive visual blink were demonstrated concurrently by EEG (N2/P2 components), MRI (integrity of optic radiations and primary visual cortex) and FDG-PET (calcarine cortex and lingual gyrus metabolism) [95 ▪ ]. Similarly, unresponsive patients able to localize auditory stimuli were found to have increased fMRI connectivity between frontoparietal and visual areas, higher alpha-band EEG connectivity, and higher levels of brain metabolism than those without auditory localization [7 ▪ ].…”
Section: Multimodal Studiesmentioning
confidence: 99%